Nanomechanics of Cells and Biomaterials Studied by Atomic Force Microscopy. Issue 16 (22nd July 2015) - Kilpatrick, Jason I.; Revenko, Irène; Rodriguez, Brian J.
Abstract : The behavior and mechanical properties of cells are strongly dependent on the biochemical and biomechanical properties of their microenvironment. Thus, understanding the mechanical properties of cells, extracellular matrices, and biomaterials is key to understanding cell function and to develop new materials with tailored mechanical properties for tissue engineering and regenerative medicine applications. Atomic force microscopy (AFM) has emerged as an indispensable technique for measuring the mechanical properties of biomaterials and cells with high spatial resolution and force sensitivity within physiologically relevant environments and timescales in the kPa to GPa elastic modulus range. The growing interest in this field of bionanomechanics has been accompanied by an expanding array of models to describe the complexity of indentation of hierarchical biological samples. Furthermore, the integration of AFM with optical microscopy techniques has further opened the door to a wide range of mechanotransduction studies. In recent years, new multidimensional and multiharmonic AFM approaches for mapping mechanical properties have been developed, which allow the rapid determination of, for example, cell elasticity. This Progress Report provides an introduction and practical guide to making AFM‐based nanomechanical measurements of cells and surfaces for tissue engineering applications. Abstract : Atomic force microscopy is an indispensable tool for nanomechanical measurements of cells, cell microenvironments, and biomaterials. The mechanical properties of cells and their function are influenced by the elasticity of the extracellular matrix. Thus, understanding the nanomechanical properties is key for tissue engineering applications.